The avocado in South Africa. Producer country file - (:unkn) unknown (My University, 2019)
South Africa, a historic player on the European counter-season avocado market, is the world number four avocado supplier. The country's export potential, which proved to be in excess of 90 000 t for 2018, should continue their rapid rise in the coming years, thanks to a cultivation area which has recently seen an accelerating rate of expansion. South African professionals, faced with the rise of Peruvian competition on the European market, on which they remain 95 % dependent, are seeking to boost their competitiveness and diversify their outlets (local market, Asia, USA).
Keywords: African Research